2016
DOI: 10.1002/etc.3252
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for metal bioavailability in assessing water quality: A step change?

Abstract: Abstract-Bioavailability of metals to aquatic organisms can be considered to be a combination of the physicochemical factors governing metal behavior and the specific pathophysiological characteristics of the organism's biological receptor. Effectively this means that a measure of bioavailability will reflect the exposures that organisms in the water column actually "experience". This is important because it has long been established that measures of total metal in waters have limited relevance to potential en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 12 publications
0
44
1
1
Order By: Relevance
“…This is inconsistent with results for freshwater organisms where the pH dependency is reversed, i.e. nickel toxicity decreases with decreasing pH (Merrington et al 2016).…”
Section: Influence Of Water Quality Parameters On Nickel Toxicitycontrasting
confidence: 93%
See 1 more Smart Citation
“…This is inconsistent with results for freshwater organisms where the pH dependency is reversed, i.e. nickel toxicity decreases with decreasing pH (Merrington et al 2016).…”
Section: Influence Of Water Quality Parameters On Nickel Toxicitycontrasting
confidence: 93%
“…and the metal-species interaction at the biotic ligand/receptor (Merrington et al 2016). The specific mode of toxic action that a metal induces in an organism, and the organism's behaviour and metabolism (e.g.…”
Section: Influence Of Water Quality Parameters On Nickel Toxicitymentioning
confidence: 99%
“…When results from our experiment conflicted with published ecotoxicological studies with copper, if sufficient water chemistry was reported, we used the Bio‐Met tool to adjust for copper bioavailability differences between study conditions . Bio‐Met is a simplified bioavailability calculator that approximates the biotic ligand modeling (BLM) used in the European Union Risk Assessment Report to calculate PNECs for copper as a function pH, DOC, and calcium concentrations in different waters .…”
Section: Methodsmentioning
confidence: 99%
“…Adjustments for water hardness are available for a number of metals, namely Cd, Cr(III), Cu, Pb, Ni, and Zn (Warne et al ). However, their appropriateness has been questioned due to 1) the limited, fish‐dominated, acute toxicity data upon which the relationships were established and 2) the fact that hardness is just one of several important toxicity modifying factors for these metals (e.g., Markich et al ; Merrington et al ). Not surprisingly, the USEPA () stated that the use of a multiple parameter bioavailability model such as the BLM (see next section) for Cu would result in a more appropriate WQC than would the hardness adjustment approach.…”
Section: Strengths Limitations and Potential Applications Of Water mentioning
confidence: 99%